2007
DOI: 10.1163/156854107779969745
|View full text |Cite
|
Sign up to set email alerts
|

Improving the use of rye (Secale cereale) for nematode management: potential to select cultivars based on Meloidogyne incognita host status and benzoxazinoid content

Abstract: Six geographically diverse cultivars of rye (Secale cereale), a wheat (Triticum aestivum) cultivar and hairy vetch (Vicia villosa) cultivar unstated were screened for Meloidogyne incognita host suitability. Chemical constituents of rye can suppress M. incognita, so the rye cultivars and wheat were also tested for benzoxazinoid content to determine if rye cultivar selection could be based upon plant chemistry. There was variation in M. incognita host status among the rye cultivars. Cultivars Aroostook, Elbon, O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…It is well known that in rye DIBOA and GDIBOA are predominant in aerial parts, whereas DIMBOA and MBOA are predominant in roots (Frey et al 2009; Zasada et al 2007; Meyer et al 2009). For DIBOA and GDIBOA, compounds dominant in above-ground parts, our results are consistent with the previous study performed in the Institute of Soil Science and Plant Cultivation which reported their content in the aerial parts to be, respectively, five and two times higher than in the roots (Krzyżanowska et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that in rye DIBOA and GDIBOA are predominant in aerial parts, whereas DIMBOA and MBOA are predominant in roots (Frey et al 2009; Zasada et al 2007; Meyer et al 2009). For DIBOA and GDIBOA, compounds dominant in above-ground parts, our results are consistent with the previous study performed in the Institute of Soil Science and Plant Cultivation which reported their content in the aerial parts to be, respectively, five and two times higher than in the roots (Krzyżanowska et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Rye HX have been mainly studied in the context of their role in allelopathy (Barnes and Putnam 1987; Tabaglio et al 2008; Gavazzi et al 2010) and their toxic impact on nematodes (Zasada et al 2005, 2007; Meyer et al 2009). Makleit (2005) reported a positive correlation between DIBOA content in two Secale species ( S. cereale and S. cereanum ) and their reaction with soil salinity.…”
Section: Introductionmentioning
confidence: 99%
“…This includes a detailed examination of the giant nurse cells induced by nematodes invading the roots. Furthermore, as it appears improbable that the reduction in nematode damage in the field after fall cropping of Tachiibuki (Tateishi et al, 2008) is explained exclusively by the reduced reproduction rate of the nematodes in the oats, some reports suggest that Meloidogyne species are suppressed in an indirect way by the production of plant derivatives during cropping of gramineous nematode hosts (Sipes and Arakaki, 1997;Zasada et al, 2007). Therefore, it is important to characterize in detail the nematode-suppressive factors involved in the cultivation of sweet potato in combination with fall cropping of Tachiibuki under field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Rye cultivars with higher root concentrations of methoxy-substituted benzoxazinoids had the lowest numbers of M. incognita eggs. These cultivars were therefore suggested for soil incorporation as green manure to protect against root-knot nematodes (Zasada et al, 2007). In a greenhouse trial, soil infested with the root-knot nematode Meloidogyne incognita was treated with DIBOA (2,4-Dihydroxy-2H-1,4-benzoxazin-3(4H)-one) at concentrations ranging from 1.1 to 18 µg/g dry soil, and M. incognita egg production in cucumber roots decreased significantly at the highest concentration (Meyer et al, 2009).…”
Section: Nematicidal/inhibitory Root Compoundsmentioning
confidence: 99%